Modern methods of treating neurological diseases - Krzysztof Bednarz; Bartosz Basiaga; Sara Trojan; Marek Leśniak; Jakub Kwieciński; Sławomir Miszuda; Agnieszka Błaszczyk; Urszula Fussek-Styga; Agata Szwedkowicz; Jakub Heluszka (Nicolaus Copernicus University in Toruń, 2023)
Aim of the article The aim of the article is to summarize the current state of knowledge about brain-computer interfaces (BCI), i.e. systems that allow you to control electronic devices by recording the activity of nerve cells. Materials and methods The article is based on a literature review in the PubMed database. Conclusions Disorders of the nervous system pose a great therapeutic challenge due to the limited regenerative capacity of the nervous tissue. In the future, BCI may become an opportunity to improve the quality of life of patients with neurological diseases. Thanks to technological progress and increasing abilities in the field of physiology of neurons, the possibilities of using this system are increasing. Clinical trials have been performed on patients with various types of neurological deficits, including movement disorders and aphasia. Brain-computer interfaces can also help with vision loss, epilepsy, and many other conditions